PENGARUH EKSTRAK DAUN MIMBA TERHADAP PERKEMBANGAN HAMA Callosobruchus chinensis L. (Coleoptera : Bruchidae) - Yustina Maria Silvia Wonga Puu; Hildegardis Nalti Nansi (AGRICA, 2019)
Callosobruchus Chinensis is a pest that damages mung bean seeds in storage and causes damage to both the quality and quantity of seeds. This study aims to determine the effectiveness of neem leaf extracts in suppressing the development of the Callosobruchus Chinensis pest as one of the postharvest pests in the commodity green beans. This research conducted at the Laboratory of the Faculty of Agriculture, University of Flores, by using a Completely Randomized Design (CRD) with five treatments and three replications. The concentration of neem leaf extract treatment is 0 ml / l, 25 ml / l, 30 ml / l, 35 ml / l, and 40 ml / l. The results showed that the concentration of neem leaf extract 40 ml / l caused mortality of C. Chinensis imago as contact poison by 99% and nerve poison by 47%. While the effectiveness of the limb leaf extract on spawning activity was 86%.